Mending our nets: Toward a feminist vision of redemption and Labrador in dialogue with the Newfoundland fishery - Brewer, Darlene (University of Ottawa (Canada), 2008)
This thesis looks toward the construction of a contextual understanding of redemption in light of women's experiences in the Newfoundland and Labrador 1 (NL) fishery. Specifically, I consider how we might speak about redemption in a way that is meaningful to their experiences in the midst of the 1990s fishery closure in the province. With the closure of the fishery there has been much loss in the way of personal and cultural identity, belief and way of life. There have been many economic, social, ecological and cultural impacts on women and men and the whole ecological system of the fishery. Women's experiences in the wake of the impact of the closure of the NL fishery make a significant contribution to a contextual understanding of redemptive hope. The Christian language of redemption is appropriate for an understanding of how we speak, theologically, about social and ecological hope. Redemption is embodied in an earthly hope, given by God and embodied in action toward the building of communities of solidarity and an ethical approach rooted in the here and now of people's everyday lives. Redemption also involves an eschatological horizon where the Mystery of God's creative and redemptive love is beyond our imagining. This promise is made known to us historically through our lived experience. Both dimensions of redemption are relevant to a construction of redemption in light of women's experiences. In the NL fishery context, the language of redemptive hope is especially pertinent in light of women's experiences of personal and community loss and devastation. This devastation is also ecological because of foreign, and, to a lesser extent, domestic overfishing that has led to the closure of the fishery and the almost non-renewability of a species---northern cod. Fundamentally, how we speak about our salvation as human beings is inextricably linked with the whole ecological well-being of our local and global communities. Theological discourse, especially around salvation and our human participation in it, fails to have meaning if it is not directly connected with our earthly, historical realities, especially in relation to experiences in times of crisis. I have chosen to focus solely on insights from women's experiences in the fishery because women's experiences as fish plantworkers and fishers are rarely highlighted. From the methodologies of feminist and liberation theologies, an experience of redemption or liberation begins with the action of God in the history of those most excluded in our societies, whose voices have not been heard. Ecofeminist theologians explore theological constructions from ecological perspectives, citing the earth itself as our place of salvation. There are many theologians who have written about redemption from liberation and ecofeminist perspectives. I will draw from three theologians---Edward Schillebeeckx, Ivone Gebara and Rosemary Radford Ruether---to consider how they speak about a socially-engaged redemption. In dialogue with these theologians' insights on redemption, I use NL women's narratives, from the fields of sociology and health, to consider women's voices during the years immediately following the closure of the fishery. Then, I consider these narratives and what they are saying theologically, individually and collectively. Specifically, I choose to articulate an understanding of redemption out of the particular context of women's lives in a fishery closure. It is my finding that these women's narratives, in dialogue with theologians' insights, contribute to a new way of speaking about redemption for today. I hope this thesis will contribute to new ways of speaking about NL women's experiences in the fishery and the fishery itself and consider new avenues for discourse on contextual, lived experiences of redemptive hope. It is a contextual understanding of this particular context and as such is one avenue of bringing the complex notion of redemption into view. It does not intend to offer a comprehensive treatment of redemption. In the context of the NL fishery I speak about the possibility of community building and ecological sustainability. These are two major components of a vision of redemptive living in the NL fishery. By taking these women's experiences into account and the reality of the ecological community of the whole fishery, I consider our redemptive hope from the perspective of interdependence of human with other life. With this development of a contextual theology around redemption in the NL fishery, I also reconstruct an understanding of the person of Jesus Christ and God born out of dialogue with theologians and women's experiences in the fishery. This new theological understanding of redemption involves the cultivation of resistance and resilience as modes of redemptive living. This is the major finding of the thesis and shapes a contextual, earth-centred, creation-focussed theology of redemption. 1In this thesis, I will refer to Newfoundland and Labrador in its abbreviated form as NL except when citing another source.
Keywords: Women's Studies.; Theology.; Agriculture, Fisheries and Aquaculture.